Pendampingan Perancangan Masterplan Wisata Dusun Sambilegi Lor, Kalurahan Maguwoharjo, Kabupaten Sleman dengan Pendekatan Partisipatif : indonesia - Handoko, Jarwa Prasetya Sih; Abma, Vendie (UII, 2026)
This community service program is located in Sambilegi Lor Hamlet, Maguwoharjo Village, Depok District, Sleman. The development of the tourism industry in Sleman Regency has increased along with the increase in tourist visits to Yogyakarta. This prompted the Maguwoharjo Village government, in this case the Sambilegi Lor hamlet, to take the initiative to develop village tourism in Sambilegi Lor Hamlet. This initiative is supported by various potentials owned by the Sambilegi Lor Hamlet community, both physical and non-physical potential of the local community that have the potential to be developed into a new tourist destination. The main problems faced by partners related to the development of the physical and non-physical potential of the community and also the development of new village tourism in Sambilegi Lor Hamlet include the unavailability of places to market and products of goods and services produced by community groups and places to perform arts groups operating in Sambilegi Lor Hamlet. The next problem is the unavailability of village tourism objects or facilities in Sambilegi Lor Hamlet. The purpose of this activity is to prepare a Tourism Masterplan that realizes the area as a new tourist destination that can attract visitors to Sambilegi Lor Hamlet, so that in the end it also facilitates the marketing process of goods and services produced by the local community. The stages of this community service activity consist of the pre-implementation stage and the implementation stage, by applying the Participatory Rural Appraisal method in its implementation. The output of this community service activity consists of outputs aimed at the Sambilegi Lor Hamlet community, including the fulfillment of the needs of the Village Tourism Masterplan design in Sambilegi Lor Hamlet and the mandatory output of this Community Service Program is in the form of publication in the National Journal.